SMART AND GOOD CITIZENS IN THE DIGITAL ERA: A PHILOSOPHICAL ANALYSIS OF UDIN S. WINATAPUTRA’S CIVIC EDUCATION PARADIGM - Roul Alvaro Prasetyo; Suyato Suyato; Wahyu Cahyana Putra (SOSIOEDUKASI, 2025)
The rapid development of technology and the growing complexity of citizenship challenges in the digital era highlight the need to revitalise Civic Education based on a strong philosophical foundation. This study analyses Udin S. Winataputra’s philosophical framework on the concept of smart and good citizenship and examines its relevance for strengthening Civic Education in Indonesia. Using a qualitative library research method, this study draws primarily from Winataputra’s 2001 dissertation and supplements it with contemporary scholarly works on citizenship, digital literacy, and civic virtue. The findings show that Winataputra’s concept integrates cognitive competencies (smart) with moral–character dispositions (good), forming a holistic paradigm for civic development. This dual framework aligns with global discussions on transformative citizenship, digital ethics, and democratic education. The study concludes that Winataputra’s philosophical contributions provide a significant foundation for redesigning Civic Education to cultivate responsible, critical, and ethically aware citizens in the digital age. Implications for curriculum development and digital citizenship education are also discussed.